Hegel and the Philosophy of Religion - Christensen, Darrel E. author. aut Link
300 p.
Keywords: THE WOFFORD SYMPOSIUM: ITs PURPOSE, GENESIS, AND THEME The purpose of The Wofford Symposium was to stimulate original scholarship on the theme of the meeting, to provide a forum in philosophy of high quality in the area which Wofford College principally serves, and to make available for publication this collection of papers, which it was felt would meet a peculiar need in the contemporary literature of philosophy. In April, 1967, I attended the annual meeting of the Metaphysical Society of America at Purdue University. Noting the frequency with which Hegel was brought into the discussions at that meeting, I was led on two occasions to inject the question into informal group discussions in the halls, "Isn't it time some sort of symposium on Hegel was held?" On the last occasion Professor Frederick Weiss replied, "Why don't you start it?" I'm not yet certain how serious the remark was intended to be, but after waiting two months, half expecting to hear of a plan under way, it occurred to me that perhaps what was wanting was a concrete proposal.